Hepatoprotective Activity of the Total Saponins from Actinidia valvata Dunn Root against Carbon Tetrachloride-Induced Liver Damage in Mice. (6th November 2012) - Qu, Liping; Xin, Hailiang; Zheng, Guoyin; Su, Yonghua; Ling, Changquan
Abstract : The protective activity of the total saponins from Actinidia valvata Dunn root (TSAV) was studied against carbon-tetrachloride- (CCl4 -) induced acute liver injury in mice. Mice were orally administered TSAV (50, 100, and 200 mg/kg) for five days and then given CCl4 . TSAV pretreatment significantly prevented the CCl4 -induced hepatic damage as indicated by the serum marker enzymes (AST, ALT, and ALP). Parallel to these changes, TSAV also prevented CCl4 -induced oxidative stress by inhibiting lipid peroxidation (MDA) and restoring the levels of antioxidant enzymes (SOD, CAT, GR, and GPX), GSH and GSSG. In addition, TSAV attenuated the serum TNF- α and IL-6 levels and inhibited the serum iNOS and NO levels. Liver histopathology indicated that TSAV alleviated CCl4 -induced inflammatory infiltration and focal necrosis. TSAV (200 mg/kg) also significantly decreased Bak, Bax mRNA and Fas, FasL, p53, and NF- κ B p65 protein expressions and increased Bcl-2 mRNA and protein expressions. Meanwhile, TSAV significantly downregulated caspase-3 and caspase-8 activities and prevented CCl4 -induced hepatic cell apoptosis. In addition, TSAV exhibited antioxidant activity through scavenging hydroxyl and DPPH free radicals in vitro . These results indicated that TSAV could protect mice against CCl4 -induced acute liver damage possibly through antioxidant, anti-inflammatory activities and regulating apoptotic-related genes.